Can We Identify Patients with High Risk of Osteoarthritis Progression Who Will Respond to Treatment? A Focus on Epidemiology and Phenotype of Osteoarthritis - Bruyère, Olivier (2022)
Publisher Copyright: © 2015, The Author(s).